Legal Implications of Minimum Education Requirements for DPR Candidates in the Perspective of the 1945 Constitution and Constitutional Court Decisions - Budi Handayani; Muchamad Taufiq; Yusuf; Fatma Faisal; Mohammad Solekhan (International Journal of Health, Economics, and Social Sciences (IJHESS), 2025)
The establishment of a minimum education requirement for candidates of the House of Representatives (DPR) has become a complex legal issue, sparking debates between the principles of meritocracy and the fulfillment of citizens’ constitutional rights. On one hand, educational qualifications are considered essential to ensure the intellectual capacity, rationality, and legislative competence of parliamentary members in performing their lawmaking and supervisory functions. On the other hand, such provisions may lead to discrimination against citizens who lack access to adequate formal education, thereby restricting their constitutional right to be elected as guaranteed under the 1945 Constitution of the Republic of Indonesia. This article aims to thoroughly examine the legal implications of establishing a minimum education requirement for DPR candidates from the perspective of the 1945 Constitution and the Constitutional Court’s jurisprudence. Using a normative juridical approach, this study analyzes the compatibility of educational restrictions with the principles of equality before the law, political rights, and constitutional democracy. The findings reveal that educational qualifications should not be perceived as discriminatory limitations but rather as instruments to ensure competence and integrity within the legislative body as part of a democratic rule-of-law system. Nevertheless, such restrictions must be formulated proportionally, clearly, and in accordance with constitutional objectives so as not to violate the principle of equality before the law or the fundamental right of citizens to participate in governance. Therefore, any regulation regarding educational requirements for DPR candidates must strike a balance between the need for legislative professionalism and the protection of citizens’ constitutional rights.